Junk: Overeating and obesity and the neuroscience of addiction - Fraser, Suzanne (Routledge, 2013)
Over the past decade intense concern has developed in the West about what has been characterised as an obesity epidemic. This concern is producing a range of effects, including changing attitudes towards food. Some foods are no longer just foods; they are increasingly framed as illicit substances. At the same time, overeating is coming to be seen as a form of addictive behaviour. How do new concerns about junk food, health and overeating impact on notions of drug use and addiction? In this article, I explore food and obesity as a case study of changing ideas about addiction. Drawing on an analysis of scientific journal articles that link obesity and addiction, the article examines the assumptions that drive such linkages, and their implications and effects. Wherever obesity is linked to addiction, this link is increasingly explained via neuroscientific theories of behaviour. The brain's hedonic and reward systems are cited to frame ‘excessive’ eating as addictive behaviour, and ‘highly palatable’ or junk foods as akin to conventional drugs. In the process, a range of phenomena are enacted. In science studies theorist John Law's [(2011). Collateral realities. In P. Baert & F. Rubio (Eds.), The politics of knowledge (pp. 156–178). London and New York: Routledge] terms, numerous important ‘collateral realities’ are produced. ‘Drug addiction’ is referred to as though no controversy exists over its interpretation. Likewise, ‘drugs’ are produced as a homogeneous group with no differentiating features. The article concludes by considering the limitations of such accounts of food, the body, health and well-being, and their reciprocal effects on the field of drug addiction.